2014
DOI: 10.1093/humrep/deu066
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemic conditions perturb mouse oocyte in vitro developmental competence via beta-O-linked glycosylation of Heat shock protein 90

Abstract: This work was supported by a programme grant from the National Health and Medical Research Council, Australia, ID 453556. J.G.T. is a recipient of funding from and a consultant to Cook Medical Pty Ltd. The other authors have no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 92 publications
0
23
0
Order By: Relevance
“…Columns with different letters differ significantly (P , 0.05, one-way ANOVA followed by a Bonferroni post hoc test). GlcN, glucosamine. to stimulate HBP and UDP-GlcNAc production (Pantaleon et al 2010;Frank et al 2014aFrank et al , 2014b. The addition of lipid to the medium did not increase O-GlcNAcylation levels.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Columns with different letters differ significantly (P , 0.05, one-way ANOVA followed by a Bonferroni post hoc test). GlcN, glucosamine. to stimulate HBP and UDP-GlcNAc production (Pantaleon et al 2010;Frank et al 2014aFrank et al , 2014b. The addition of lipid to the medium did not increase O-GlcNAcylation levels.…”
Section: Discussionmentioning
confidence: 90%
“…Glucosamine (GlcN), a known hyperglycaemic mimetic, can be metabolised via the HBP by bypassing the rate-limiting enzyme of the HBP, namely glutamine:fructose-6-phosphate amidotransferase (GFPT; Nelson et al 2000;Uldry et al 2002); hence, it is a potent stimulator of HBP pathway activity. Previously, we demonstrated that GlcN supplementation during IVM results in increased O-GlcNAcylation in mouse COCs (Frank et al 2014a) and perturbed oocyte developmental competence in cow, pig and mouse and decreased cleavage rates in the mouse (Sutton-McDowall et al 2006;Kimura et al 2008;Schelbach et al 2012;Frank et al 2013).…”
Section: Introductionmentioning
confidence: 86%
“…In this way, the PPP also controls the oxidative status of the oocyte by producing nicotinamide adenine dinucleotide phosphate (NADPH) as a cofactor for lipid, steroid, and nucleic acid synthesis (65). Additional glucose enters the hexosamine biosynthesis pathway to provide substrate for hyaluronic acid production during extracellular matrix expansion and O-linked protein glycosylation for cell signaling and fuel sensing (61,66). Excess glucose shunted through the polyol pathway produces fructose and sorbitol in hyperglycemic conditions, with negative consequences for oocyte quality (61).…”
Section: Cellular Metabolism Glucose Metabolismmentioning
confidence: 99%
“…Reduced glucose flux through the PPP in COCs from diabetic mice (207) also impairs oocyte development (208,209) by decreasing purine and cAMP synthesis (207), with excess glucose shunted through the polyol pathway (210). Activation of the hexosamine biosynthetic pathway in mouse COCs exposed to glucosamine further increases protein beta-O-linked glycosylation (O-GlcNAcylation) that can damage embryo development (66,209). Glycolytic activity is also partially blocked in some diabetic oocytes that exhibit increased glycogen and fructose-1,6-phosphate levels as proximal glycolytic metabolites and low ATP concentrations (211).…”
Section: Metabolic Dysfunction Obesitymentioning
confidence: 99%
“…Moreover, increasing HBP pathway flux by glutamine treatment to elevate O-GlcNAc enhances expression of HSF1 and HSP70 in a septic mouse model and in isolated rat cardiomyocytes (32,61). HSP70 and HSP90 are modified by O-GlcNAc (62,63). Additionally, HSP70 displays lectin-like binding activity specifically toward O-GlcNAc (64), and HSP90 inhibition destabilizes OGT and reduces O-GlcNAcylation (65).…”
Section: O-glcnac and Cancer Cell Survivalmentioning
confidence: 99%